2011
DOI: 10.1159/000333211
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of HBsAg Seroclearance in HBeAg-Negative Chronic Hepatitis B Patients

Abstract: Background and Aims: In chronic hepatitis B virus (HBV) infections, hepatitis B surface antigen (HBsAg) seroclearance reportedly occurs at a rate of 0.50–2.26%. Several factors were suggested to be associated with seroclearance including age and HBeAg negativity. However, there are few studies evaluating whether HBV DNA levels are an independent predictor of HBsAg seroclearance. The aim of this study was to evaluate the annual HBsAg seroclearance rate and its predictors including serum HBV DNA levels in HBeAg-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Accompanied with qHBsAg level decreasing gradually over times, lower levels of qHBsAg or rapid reduction rate of qHBsAg would eventually lead to HBsAg seroclearance or seroconversion [16]. Another important finding was the HBV DNA level and their reductions, which had previously been considered as powerful predictors for HBsAg seroclearance in pre-qHBsAg era [6], [8]. Liu et al found that decrease in HBV DNA levels was the most important predictor of HBsAg seroclearance [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accompanied with qHBsAg level decreasing gradually over times, lower levels of qHBsAg or rapid reduction rate of qHBsAg would eventually lead to HBsAg seroclearance or seroconversion [16]. Another important finding was the HBV DNA level and their reductions, which had previously been considered as powerful predictors for HBsAg seroclearance in pre-qHBsAg era [6], [8]. Liu et al found that decrease in HBV DNA levels was the most important predictor of HBsAg seroclearance [8].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier HBsAg seroclearance or seroconversion is likely resulted in a better prognosis because of lower HBV replication as well as less liver damage [1], [2]. A few studies have explored the incidence of spontaneous HBsAg seroclearance in CHB patients of both Asian and European populations using long-term follow-up cohorts and the annual incidence ranges from 0.62% to 2.26% [3], [4], [5], [6], [7], [8]. Because of the more rarity of spontaneous HBsAg seroconversion, compared to HBsAg seroclearance, the incidence and long-term outcomes of CHB patients experiencing this event remain disputed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBs-Ag seroclearance may occur either after the acute phase that takes few months or after years of chronic infection [24,27,28]. -The seronegative OBI do not present anti-HBc and anti-HBs antibodies; anti-HBs antibodies progressively could be disappeared with an anti-HBc seroconversion over time without development of detectable HBs-Ag [24,29].…”
Section: Occult Hepatitis B Infectionsmentioning
confidence: 99%
“…A Korean study demonstrated that the overall annual HBsAg seroclearance rate was 1.8%, but the annual HBsAg seroclearance rate of the older-aged group was higher, i.e., the annual seroclearance rate was 2.69% among patients aged over 60, whereas the annual seroclearance rate was 1.91% among the patients aged between 40 and 59. The cumulative probabilities of HBsAg seroclearance were 1.2%, 3.8% and 8.7% for patients who were followed for 1, 3 and 5 years, respectively [15]. The annual HBsAg seroclearance rate in our study was 0.48%, i.e., 8 patients exhibited HBsAg seroclearance in the 1645 person-years study, and the rate was 0.3%, i.e., 5 patients exhibited HBsAg seroclearance in the 1624 person-years study.…”
Section: Discussionmentioning
confidence: 99%